Literature review: Penanganan nonfarmakologi untuk penurunan kadar gula darah pada pasien diabetes mellitus - Alfian Helmi; Nora Veri; Lina Lina (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Heart disease, stroke, neurological disease, and kidney disease, which can lead to kidney failure, are complications that occur as a result of diabetes mellitus. Nonpharmacological therapies for lowering blood glucose levels in people with diabetes mellitus are very diverse, including the consumption of natural ingredients such as ginger, bengkoang, and bay leaves proven to reduce blood glucose levels or with other interventions such as gymnastics and relaxation techniques.Objectives: This study aimed to provide knowledge regarding complementary therapies for diabetic blood glucose.Methods: The type of research is a narrative review of articles published from 2016 to 2023 using databases such as Google Scholar, PubMed, and Science. The reviewed articles were quasi-experimental studies and randomized controlled trials with data supporting non-pharmacological therapy for diabetes mellitus blood sugar levels. The data were processed and analyzed using the PRISMA approach.Results: Nonpharmacological treatments that are often used to lower blood sugar levels in patients with diabetes mellitus include gymnastics and relaxation. The results of the analysis highlighted the effect of interventions on patients with diabetes mellitus to reduce blood sugar levels before and after the provision of interventions.Conclusion: Gymnastics and relaxation techniques have the potential to reduce blood sugar levels. Nonpharmacological therapy, as a treatment to lower blood glucose in diabetes, aims to improve blood circulation, reduce muscle tension, and relax the body.